THE IMPACT OF SHARIA ECONOMIC LAW ON ECONOMIC GROWTH IN MUSLIM-MAJORITY COUNTRIES: A GLOBAL PERSPECTIVE - Imron Natsir; Ton Kiat; Rit Som (Yayasan Adra Karima Hubbi, 2025)
The principles of Sharia economic law, rooted in Islamic jurisprudence, emphasize ethical and equitable economic practices. As Muslim-majority countries increasingly adopt Sharia-compliant financial systems, understanding their impact on economic growth has become crucial. This study examines the influence of Sharia economic law on economic growth in Muslim-majority countries from a global perspective. The research aims to analyze the relationship between Sharia economic law and economic growth, identifying key drivers, challenges, and opportunities for sustainable development in Muslim-majority countries. A mixed-methods approach is employed, combining quantitative analysis of macroeconomic data from 20 Muslim-majority countries and qualitative interviews with policymakers, economists, and Sharia scholars. Data were analyzed using regression models and thematic analysis. The findings reveal that Sharia economic law positively impacts economic growth by promoting ethical investments, financial inclusion, and risk-sharing mechanisms. However, challenges such as regulatory inconsistencies, limited financial literacy, and inadequate infrastructure hinder its full potential. Countries with robust Sharia governance frameworks and supportive policies reported higher economic growth rates.